An investigation of two xylan‐degrading enzymes and a novel xylanase inhibitor in malted barley. Issue 1 (17th June 2013) - Kanauchi, Makoto; Chijimi, Ayaka; Ohnishi‐Kameyama, Mayumi; Bamforth, Charles W.
Abstract : Two enzymes with activity on xylan and xylan‐based substrates were isolated from malted barley. One appears to be relatively anionic and the other more cationic. Both are endo‐acting enzymes. The first of these was studied in more detail and shown to be of molecular weight ca. 59, 000 and capable of acting through the pH range 5–7.5. It is relatively heat tolerant, with 30% of its activity surviving for 30 min at 70 °C. A low‐molecular‐weight (ca. 1300) inhibitor of xylanase that developed during germination was investigated. Its potency was not lowered by treatment with proteolytic enzymes, but treatment with polyvinylpolypyrrolidone did reduce its impact. Ultraviolet spectrophotometry and Fourier transform infrared spectroscopy, as well as staining with Folin–Ciocalteu reagent, indicated the presence of phenolic species, while mass spectroscopy studies suggested the presence of arabinose and possibly poly‐hexose. The presence of material that stained with aniline phthalate would be consistent with the presence of reducing sugar in the inhibitor. Copyright © 2013 The Institute of Brewing & Distilling